Portrait of A Culture-Based Tourism Village - Suhaeb, Firdaus W.; Kaseng, Ernawati S. (PINISI Discretion Review, 2025)
The purpose of this research is to describe the Portrait of Kampung Rama Agung in North Bengkulu Regency which is a culture-based tourism village and contains the customary values of the local community and has a very strong tourist attraction through the diversity of traditional cultural heritage that is still maintained and maintained by the local community. The method used in this research is a literature study with a qualitative approach conducted by in-depth observation and interviews related to Rama Agung Village as a Culture-Based Tourism Village in North Bengkulu Regency. Thus, this research can describe and explain the portrait of Kampung Rama Agung as a Culture-Based Tourism Village in North Bengkulu Regency and explain the role of the local community, customary institutions, and the government in maintaining and developing Kampung Rama as a Cultural Tourism that further strengthens the social, economic, and cultural identity of the local community.